PIECES Analysis and Effect of Fikri Karya Gemilang Website Design on Promotion System Using Waterfall Model - Anwardi; Anggi Ramadona; Misra Hartati; Tengku Nurainun; Ekie Gilang Permata (Jurnal Rekayasa Sistem & Industri, 2020)
Promotion is one type of communication that is often used by marketers, as one element of the promotionalmix. The promotion process carried out by CV Fikri Karya Gemilang is a traditional promotion model,with direct visits without other alteratives. The promotion system still does not provide optimalperformance for the company's revenue. Based on data from the company, there is a decrease in jobs thatare not in accordance with the company's target and unreachable regional segmentation. This study usesthe PIECES method by analyzing the company's promotion system. This research proposes a websitedesign using the waterfall model and usability testing on the website with a total score of 0.72 whichmeans good, and the application of online media as an internet-based promotion media. This study alsolooked at the effect of the adoption of a traditional promotion system and the adoption of an internet-basedproposed promotion system using paired sample t-tests. Based on the PIECES analysis, it is found thatthere is a level of customer satisfaction with the application of a manual promotion system that is less thanoptimal, and the application of the proposed promotion system provides an increase in consumersatisfaction. Based on paired sample t-test, it can be concluded that the Sig (2-tailed) value of 0.0000015means that there is a significant difference between the application of the traditional promotion system andthe internet-based proposal promotion system.